Laboratory Utilization, Learning Independence, and Learning Motivation as Predictors of Outcomes in Electrical Education: Moderating Role of Teacher Social Competence - Redianto Nurdin; Alimuddin Sa’ban Miru; Mukhlisin (Academic Bright Collaboration, 2026)
Purpose – This study analyzes the influence of the utilization of electrical laboratory facilities, learning independence, and learning motivation on students learning outcomes, as well as examines the role of teachers' social competence as a moderating variable. Method - This study used a quantitative approach with an explanatory research type. The population consisted of 279 students, and the sample included 165 students determined through a proportional random sampling technique. Data were collected using a Likert scale questionnaire and documentation. Data analysis was performed using SEM based on Partial Least Squares (PLS) with the assistance of SmartPLS. Findings – Hypothesis testing indicates that the utilization of electrical laboratory facilities (β = 0.283; p < 0.000), learning independence (β = 0.378; p < 0.000), and learning motivation (β = 0.338; p < 0.000) positively and significantly affect learning outcomes. Additionally, teachers’social competence positively and significantly moderated the relationship between the utilization of electrical laboratory facilities (β = 0.181; p < 0.003), learning independence (β = 0.252; p < 0.000), and learning motivation (β = 0.189; p < 0.000) on learning outcomes. The coefficient of determination (R²) value of 0.555 indicates that the model can explain 55% of the variation in the learning outcomes.The research results affirm that the improvement of learning outcomes in electrical vocational education is influenced by the integration of students’ internal and external learning factors Research implications – Practically, it is necessary to optimize the use of laboratories, strengthen learning independence and motivation, and enhance teachers’ social competence to support more effective learning. Originality – This study highlights the holistic integration of internal and external factors as a key determinant of learning outcomes in electrical vocational education, providing a more comprehensive perspective compared to studies that examine these factors separately.